2013
DOI: 10.1007/s12664-013-0324-3
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertensive polyps: distinct entity

Abstract: PHP are definite identifiable lesion in patients of cirrhosis with PH. PHP are probably related to increased angiogenesis in gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…McCormack et al coined, for the first time in 1985, the term "portal hypertensive gastropathy" for congestion-related gastric mucosal alterations with no inflammation seen during endoscopy [5,6]. Although its mechanism has yet to be exactly known, it was shown to be histologically characterized by the dilatation of mucosal and submucosal gastric vessels [3,4]. Gastric mucosal response to mucosal damage alters in the stomach, and a complex of structural alterations is seen in all the components of the gastric wall in PHG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCormack et al coined, for the first time in 1985, the term "portal hypertensive gastropathy" for congestion-related gastric mucosal alterations with no inflammation seen during endoscopy [5,6]. Although its mechanism has yet to be exactly known, it was shown to be histologically characterized by the dilatation of mucosal and submucosal gastric vessels [3,4]. Gastric mucosal response to mucosal damage alters in the stomach, and a complex of structural alterations is seen in all the components of the gastric wall in PHG.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of PHG is unclear, it is held to mainly involve local or generalized alterations in vascular hemodynamics [1]. In addition to such findings, polypoid lesions in the stomach have rarely been defined as endoscopic findings in patients with liver cirrhosis [2][3][4]. The results of certain studies have revealed that such polypoid formations were characterized histologically by the dilatation in the mucosal and submucosal vessels of the stomach [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…5 These hyperplastic polyps have also been spotted in patients with portal hypertension, but they tend to exhibit a larger blood vessel diameter. 9,10 Multiple hyperplastic polyps are typically observed in the antrum. 5 Macroscopically, they are smooth and dome-shaped and usually range in size from 0.5 to 1.5 cm, although rarely may exceed 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study from Canada, only 12 cases were identified over 20 years [3]. The two studies under review, only one of them prospective, found PHP in 1.01 % to 2.53 % of patients undergoing upper endoscopy for PH over 15-33 months [1,2]. PHP are, therefore, not really uncommon, and while gastroscopy has been a routine diagnostic procedure in PH for decades now, PHP has clearly remained unappreciated till recently.…”
mentioning
confidence: 99%
“…The latest entry to this slowly lengthening list of abnormalities is the 'portal hypertensive polyp' (PHP), described in two reports in the current issue of this Journal [1,2]. As with any newly described entity, a bevy of questions immediately comes up.…”
mentioning
confidence: 99%